Corporate Governance and Firm Performance: Evidence from Textile Sector of Pakistan - Akbar, Ahsan (Journal of Asian Business Strategy, 2014)
This study is intended to examine the relationship between three important mechanisms of corporate governance (ownership concentration, board size, CEO/Chair duality) and two firm performance proxies (Return on Asset, ROA, and Return on Equity, ROE) for a sample of 12 textile firms of Pakistan listed on the Karachi stock exchange. The data ranges from 2007 to 2011.The empirical evidence indicates that ownership concentration positively affect both performance variables ROA and ROE. This is justified on the grounds that, because majority shareholders have more voting power so they can exert pressure on the management take decisions that optimize firm performance. Similarly, the study found significant positive relationship between small board size and ROA. The implication is that the board size should be limited to a sizeable number in order to avoid delays in important corporate decisions that can arise because of a larger board size. However, no significant relationship was found between board size and ROE. The empirical findings also suggest a positive significant impact of CEO/Chair duality on ROA and ROE. This indicates that because dual role enable the CEO to enjoy more autonomy and control as a result he/she can govern the firm in a way that increase the firm performance.